HIDROLISA KOLAGEN DALAM CEKER AYAM HASIL PERENDAMAN DENGAN ASAM ASETAT PADA PROSES PEMBUATAN GELATIN - Santosa, Herry; Abyor H, Noer; Guyana, Nurmy Lailati; Dwi Handono, Sigit Firman (Vocational School Diponegoro University, 2018)
Herry Santosa, Noer Abyor H, Nurmy Lailati Guyana, Sigit Firman Dwi Handono, Gelatin is a chemical compound with molecular formula (C102H151N31O39)n in the form of a heterogeneous mixture of polypeptide obtained by collagen partial hydrolysis of animal binding tissue by acid or base treatment. Sources of gelatin production generally derived from cow bones, pig skins, fish scales or chicken bones. Gelatin is widely used in food and pharmaceutical industries because of its ability to form a thermoreversible gel, among others as a stabilizer on ice cream, capsule making materials and matrix for implants. The main objective of this research is to make gelatin with chicken claw based ingredients through the process of collagen hydrolysis. Specifically aims to determine the effects of acetic acid concentration on the collagen levels, determining the most influential variable between temperature and time on the hydrolysis process, as well as the assessment and determination of the optimum temperature or time in the hydrolysis process so as to approximate the criteria corresponding to the commercial gelatin characteristics, i.e gel strength (50-300 Bloom), viscosity (1.5-7,5 cP), and gelatin sensory properties. To answer that goal, the research is planned through 2 stages, namely the preparation stage, product creation, and gelatin flour characterization. The preparatory stage consists of cleansing, reduction of chicken claw and demineralization. The production stage consists of determining the most influential variables and the optimum variable variations (temperature and time) of the collagen hydrolysis process into gelatin flour based on the functional properties and gelatin sensory properties. The results of this research showed that the optimum concentration of acetic acid in demineralization was at a concentration of 1.5 N, the most influential variable was the temperature variable with a single effect average value - 5.05, the relatively good variable collagen hydrolysis was at 600 C and 4 hour.